Clinical Laboratories – Production Factories or Specialized Diagnostic Centers (Journal of Namibian Studies : History Politics Culture, 2016)
Since a large proportion of medical decisions are based on laboratory results, clinical laboratories should meet the increasing demand of clinicians and their patients. Huge central laboratories may process over 10 million tests annually; they act as production factories, measuring emergency and routine tests with sufficient speed and accuracy. At the same time, they also serve as specialized diagnostic centers where well-trained experts analyze and interpret special test results. It is essential to improve and constantly monitor this complex laboratory service, by several methods. Sample transport by pneumatic tube system, use of an advanced laboratory information system and point-of-care testing may result in decreased total turnaround time. The optimization of test ordering may result in a faster and more cost-effective laboratory service. Autovalidation can save time for laboratory specialists, when the analysis of more complex results requires their attention. Small teams of experts responsible for special diagnostic work, and their interpretative reporting according to predetermined principles, may help to minimize subjectivity of these special reports. Although laboratory investigations have become so diversely developed in the past decades, it is essential that the laboratory can provide accurate results relatively quickly, and that laboratory specialists can support the diagnosis and monitoring of patients by adequate interpretation of esoteric laboratory methods.